2020
DOI: 10.3390/met10020222
|View full text |Cite
|
Sign up to set email alerts
|

Liquation Cracking Tendency of Novel Al-Mg-Zn Alloys with a Zn/Mg Ratio below 1.0 during Fusion Welding

Abstract: The main obstacle for the application of high strength 7××× series aluminum alloys is that these alloys are susceptible to hot cracking during fusion welding. This study presents the liquation cracking susceptibility of the novel T-Mg32(AlZn)49 phase strengthened Al-Mg-Zn alloy with a Zn/Mg ratio below 1.0 by a circular-patch welding test, and compared the liquation cracking tendency with η-MgZn2 phase strengthened 7××× series alloys whose Zn/Mg ratios are above 1.0. It was found that all these novel Al-Mg-Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…[33,37] and systematic investigations in this study, the mechanisms contributing to hot tearing in Al 3 Mg 2 and T-Mg 32 (Al,Zn) 49 are different. Al 3 Mg 2 can cause stress concentration and continuous cracking along the interdendritic channel, whereas T-Mg 32 (Al,Zn) 49 leads to reduced interdendritic liquid feeding capability [33]. √ " mark means visible, and their contribution to HTS.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…[33,37] and systematic investigations in this study, the mechanisms contributing to hot tearing in Al 3 Mg 2 and T-Mg 32 (Al,Zn) 49 are different. Al 3 Mg 2 can cause stress concentration and continuous cracking along the interdendritic channel, whereas T-Mg 32 (Al,Zn) 49 leads to reduced interdendritic liquid feeding capability [33]. √ " mark means visible, and their contribution to HTS.…”
Section: Discussionmentioning
confidence: 59%
“…Because the Zn content of the alloy was approximately 0 wt.%, much lower than the 0.68-0.70 wt.% required for T-Mg32(Al,Zn)49 to form both grain boundaries and within grains [28], T-Mg32(Al,Zn)49 predominantly formed at gr boundaries, and such formation impeded liquid flow, which has also been observed ref. [33]. Consequently, the feeding capability of 5C was low, leading to a high HTS val By comparing the microstructural and HTS differences between 5b and 5C, the effects Al3Mg2 and T-Mg32(Al,Zn)49 on hot tearing could be understood.…”
Section: Influence Of Compositional Variation On Microstructurementioning
confidence: 99%
“…Additionally, research has shown that these alloys have a good adaptability to casting, plastic deformation, and additive manufacturing [8,16,17], and have a satisfactory weldability [18]. These excellent characteristics indicate that Al-Mg-Zn-Cu alloys with low Zn/Mg ratios have promising application prospects in the automotive industry [6,7].…”
Section: Introductionmentioning
confidence: 99%